Recovery of severely ill COVID-19 patients by intravenous immunoglobulin (IVIG) treatment: A case series - Mohtadi, Negar (Virology, 2020)
INTRODUCTION: During the recent months, COVID-19 has turned to a global crisis claiming high mortality and morbidity among populations. Despite the high prevalence of the disease, it has currently no definitive treatment. We here reported the effects of intravenous immunoglobulin (IVIG) administration in severely ill COVID-19 patients diagnosed based on PCR and radiology tests. CASE PRESENTATION: Five severely ill COVID-19 patients in whom standard treatments failed were administrated with IVIG which prevented the deterioration of clinical symptoms. All the patients were treated with high-dose IVIG (0.3–0.5 g/kg) for 5 consecutive days so that no patient would receive lower than 25 g of the drug. All the patients showed a desirable therapeutic response and were discharged from the hospital with a stable clinical condition after being recovered. CONCLUSION: Treatment with IVIG at the therapeutic dose of 0.3–0.5 g/kg can improve the clinical condition and O2 saturation and prevent the progression of pulmonary lesions in COVID-19 patients with severe symptoms in whom standard treatments have failed.